Sistem Pendukung Keputusan Pegawai Berprestasi Pada KSPPS BMT ALHIKMAH Weleri Dengan Metode SAW (Simple Addtive Weighting) - NUR ROKHMAN; Edy Siswanto; Nia Novitasari (JURNAL TEKNIK INFORMATIKA DAN MULTIMEDIA, 2021)
Employee Performance Assessment is used to evaluate the work of all employees or employees either quantitatively or qualitatively. Sometimes the problem of subjectivity in employee performance appraisals is often unavoidable, making it difficult to measure the parameters in the system. Based on this, to help determine the employee's work performance assessment, a decision support system is needed that can provide appropriate results in employee performance with predetermined criteria including Work Spirit, Discipline, Work Results, Responsibility. Based on the description, the author proposes to make "Decision Support System for Outstanding Employees at KSPPS BMT Alhikmah Weleri Using the SAW (Simple Additive Weighting) Method". The SAW method used is to create a decision support system for outstanding employees, especially for KSPPS BMT Alhikmah Weleri employees, so that in the future accurate results can be obtained in assessing employee performance.